Design and analysis of fully differential CMOS LNA for 3.110.6GHZ UWB communications systems / Noorinani Taib - Taib, Noorinani (2009)
In this thesis, a CMOS Ultra-wideband (UWB) Low Noise Amplifier (LNA) was designed and simulated. In the design, specific architecture decisions were made in consideration. An ultra-wideband (UWB) 3.1-10.6GHz low noise amplifier adopts crosscoupling common-gate (CG) topology is presented in this thesis. Inductive seriespeaking is used for the LNA to obtain broadband flat gain in the whole 3.1-10.6GHz band. Designed in a commercial 0.18um CMOS technology, the LNA achieves an noise figure of 3.1-4.7 dB, an input return loss (Sll) of less than -lOdB, an S21 of 10.3dB and input 3rd interception point (IIP3) of -5.1dBm, while the power supply is 1.8V.